2010
DOI: 10.1108/13527601011068360
|View full text |Cite
|
Sign up to set email alerts
|

Management practices of Chinese managers in Chinese MNCs operating in Bangkok

Abstract: Purpose -The purpose of this paper is to analyze Thai and Chinese national characteristics based on Hofstede' s cultural dimensions, Chinese human resource management approaches, and Thai and Chinese social concepts. Design/methodology/approach -The data for the analysis were obtained by surveying MBA students currently working in Chinese multinational companies and studying in public and private universities in Bangkok, using purposive sampling along with snowball sampling method. The design of the questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
5
2
Order By: Relevance
“…There is an expected social hierarchy in Thailand (Pongsapich, 1998; Swierczek and Onishi, 2002). The result relates to Thais who require explicit instruction about team leadership and authorized persons when working in a team (Banchapattanasakda and Wong, 2010). Moreover, Thai subordinates accept that the company should have clear hierarchy and certain distance should be kept for employees based on respect (Swierczek and Onishi, 2002).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an expected social hierarchy in Thailand (Pongsapich, 1998; Swierczek and Onishi, 2002). The result relates to Thais who require explicit instruction about team leadership and authorized persons when working in a team (Banchapattanasakda and Wong, 2010). Moreover, Thai subordinates accept that the company should have clear hierarchy and certain distance should be kept for employees based on respect (Swierczek and Onishi, 2002).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Chinese expatriates have been sent to Thailand for management control purpose and to develop Thai coworkers. Thus, Chinese MNCs not only bring in capital and technologies to Thailand but also their managerial cultures and practices (Banchapattanasakda and Wong, 2010). The increased number of Chinese-related companies operating in Thailand and the expected growing volume of trade and investment between the China and Thailand means that it is important to understand the effect that cultural relationships between expatriates Chinese and Thais may have on organization performance.…”
Section: Introductionmentioning
confidence: 99%
“…The study results supported previous evidence that EMNCs localised their employee relations under the subsidiary country's Labour Act and following the International Labour Organisation (ILO) laws (Adams et al 2017). However, the findings stand in contrast with the study conducted by Bunchapattanasakda and Wong (2010) on management practices in Chinese MNCs operating in Bangkok, which found that the parent companies had not factored labour relation practices, aspects or customs in the targeted host country into their location decision.…”
Section: Employee Relations/trade Unionscontrasting
confidence: 99%
“…While it is beyond the confines of this article in providing an exhaustive review of these works, a vignette review of the articles published in Cross Cultural Management in recent years (2007)(2008)(2009)(2010)(2011) sufficiently illustrates the wealth of offerings beyond purely cultural explanations of ethnonational differences. Among which, the most positive insights are presented by calls for moving the focus of cross-cultural research away from the preoccupation with proving the superiority of one set of cultural attributes over another (Bunchapattanasakda and Wong, 2010;Migliore, 2011;Yuan, 2010). Most of these works urge for an analytical lens that is current with the times; namely, focusing on integrating the strengths of global cultural diversity and moving beyond enacting dichotomies.…”
Section: Introductionmentioning
confidence: 99%